Educational Implications on Professional Stress and Its Scope: - (Journal of Advances and Scholarly Researches in Allied Education, 2012)
This hierarchical vision of social diversity draws onwhat Sleeter and Grant (1988) call a "deficiency orientation."Problems exist for those who are "different" from the norm--for limitedEnglish speakers, students of color, and so on. Learners were seen as varyingin the degree to which they differed from the norm. Respondents often describedin apparently sympathetic tones the" victims" of difference, theirneed for self-esteem, and a reaffirmation of their "right" toeducation.